CDC2 mediates progestin initiated endometrial stromal cell proliferation: a PR signaling to gene expression independently of its binding to chromatin. - Griselda Vallejo; Alejandro D La Greca; Inti C Tarifa-Reischle; Ana C Mestre-Citrinovitz; Cecilia Ballaré; Miguel Beato; Patricia Saragüeta (PLoS ONE)
Although non-genomic steroid receptor pathways have been studied over the past decade, little is known about the direct gene expression changes that take place as a consequence of their activation. Progesterone controls proliferation of rat endometrial stromal cells during the peri-implantation phase of pregnancy. We showed that picomolar concentration of progestin R5020 mimics this control in UIII endometrial stromal cells via ERK1-2 and AKT activation mediated by interaction of Progesterone Receptor (PR) with Estrogen Receptor beta (ERb) and without transcriptional activity of endogenous PR and ER. Here we identify early downstream targets of cytoplasmic PR signaling and their possible role in endometrial stromal cell proliferation. Microarray analysis of global gene expression changes in UIII cells treated for 45 min with progestin identified 97 up- and 341 down-regulated genes. The most over-represented molecular functions were transcription factors and regulatory factors associated with cell proliferation and cell cycle, a large fraction of which were repressors down-regulated by hormone. Further analysis verified that progestins regulate Ccnd1, JunD, Usf1, Gfi1, Cyr61, and Cdkn1b through PR-mediated activation of ligand-free ER, ERK1-2 or AKT, in the absence of genomic PR binding. ChIP experiments show that progestin promoted the interaction of USF1 with the proximal promoter of the Cdc2 gene. Usf1 knockdown abolished Cdc2 progestin-dependent transcriptional regulation and cell proliferation, which also blocked Cdc2 knockdown. We conclude that progestin-induced proliferation of endometrial stromal cells is mediated by ERK1-2 and AKT dependent early regulation of USF1, which directly induces Cdc2. To our knowledge, this is the first description of early target genes of progestin-activated classical PR via crosstalk with protein kinases and independently of hormone receptor binding to the genomic targets.